SAG/RBX2 E3 Ubiquitin Ligase Differentially Regulates Inflammatory Responses of Myeloid Cell Subsets - Xiong, Xiufang; Mathewson, Nathan D.; Li, Hua; Tan, Mingjia; Fujiwara, Hideaki; Li, Haomin; Reddy, Pavan; Sun, Yi (Frontiers in Immunology, 2018)
Macrophages form an important component of the innate immune system and serve as first responders against invading pathogens. While pathways critical for initiation of inflammatory responses between macrophages and other LysM+ myeloid cells are largely similar, it remains unknown whether a specific pathway has differential effects on inflammatory responses mediated between these cells. Recent studies demonstrated that depletion of SAG (Sensitive to Apoptosis Gene), an E3 ubiquitin ligase, blocked inflammatory responses generated by macrophages and dendritic cells in response to LPS in cell culture settings. However, the in vivo role of Sag on modulation of macrophages and neutrophil is not known. Here we generated LysM-Cre/Sagfl/fl mice with selective Sag deletion in myeloid lineage, and found that in contrast to in vitro observations, LysM-Cre/Sagfl/fl mice showed increased serum levels of proinflammatory cytokines and enhanced mortality in response to LPS. Interestingly, while Sag-/- macrophages released less proinflammatory cytokines, Sag-/- neutrophils released more. Mechanistically, expression of a list of genes response to LPS was significantly altered in bone marrow cells from LysM-Cre+/Sagfl/fl mice after LPS challenge. Specifically, induction by LPS of myeloperoxidase (Mpo), a key neutrophil enzyme, and Elane, neutrophil expressed elastase, was significantly decreased upon Sag depletion. Collectively, our study revealed that Sag plays a differential role in the activation of macrophages and neutrophils.